2022
DOI: 10.1029/2021je006916
|View full text |Cite
|
Sign up to set email alerts
|

Space Weathering Effects in Troilite by Simulated Solar‐Wind Hydrogen and Helium Ion Irradiation

Abstract: Space weathering is a key process in the interpretation of airless planetary surfaces. As we engage new missions to planetary objects with potentially novel surfaces such as 16 Psyche, there is renewed interest in expanding our knowledge of space weathering effects to a wider variety of analog materials, including the physical/chemical effects of solar‐wind ions on planetary regoliths. We have experimentally simulated the effects of solar ions on two polished thick sections of meteoritic troilite (FeS) via irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 120 publications
0
11
0
Order By: Relevance
“…SDTrimSP‐3D represents a three‐dimensional expansion of SDTrimSP and allows the implementation of a surface morphology or more complex structures on a grid of cuboid voxels. SDTrimSP is often used for studying ion‐surface interaction in nuclear fusion research (Oberkofler et al., 2015; Schmitz et al., 2018; Sugiyama et al., 2016), and has also been applied for simulating systems relevant to space weathering to better understand sputtering (Morrissey et al., 2022; Schaible et al., 2017; Szabo, Biber, Jäggi, Brenner, et al., 2020; Szabo, Biber, Jäggi, Wappl, et al., 2020), ion implantation (Biber et al., 2020), or ion‐induced surface composition changes (Christoph et al., 2022). The scattering of ions from surfaces has also been compared to SDTrimSP simulations by Deuzeman (2019), finding a good agreement with experimental data for several cases.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…SDTrimSP‐3D represents a three‐dimensional expansion of SDTrimSP and allows the implementation of a surface morphology or more complex structures on a grid of cuboid voxels. SDTrimSP is often used for studying ion‐surface interaction in nuclear fusion research (Oberkofler et al., 2015; Schmitz et al., 2018; Sugiyama et al., 2016), and has also been applied for simulating systems relevant to space weathering to better understand sputtering (Morrissey et al., 2022; Schaible et al., 2017; Szabo, Biber, Jäggi, Brenner, et al., 2020; Szabo, Biber, Jäggi, Wappl, et al., 2020), ion implantation (Biber et al., 2020), or ion‐induced surface composition changes (Christoph et al., 2022). The scattering of ions from surfaces has also been compared to SDTrimSP simulations by Deuzeman (2019), finding a good agreement with experimental data for several cases.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…In addition, other laboratory simulations of solar wind irradiation of troilite employed X-ray photoelectron microscopy (XPS) to reveal the preferential sputtering of sulfur from the surface of the sulfide during 4 keV He + and Ar + ion irradiation experiments (Loeffler et al 2008 ). Moreover, Christoph et al ( 2022 ) identified sulfur depletion after 1 keV H + and 4 keV He + irradiation of troilite from Canyon Diablo and Toluca meteorites using XPS and performed the collisional simulations on the Static and Dynamic Trim for Sequential and Parallel computer (SDTrimSP) software to identify the physical factors contributing to the sulfur depletion. The simulations show that by adding radiation-enhanced diffusion on the model, the fit between the concentrations of Fe and S obtained from SDTrimSP and the concentrations identified in the XPS data improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The simulations show that by adding radiation-enhanced diffusion on the model, the fit between the concentrations of Fe and S obtained from SDTrimSP and the concentrations identified in the XPS data improved significantly. During radiation-enhanced diffusion, ion irradiation creates defects in the target lattices (i.e., vacancies and interstitials) (Betz and Wehner 1983 ) that promote the diffusion of volatile species towards the surface where they are subsequently sputtered (Christoph et al 2022 ). This suggests that in addition to sputtering, radiation-enhanced diffusion might enhance sulfur loss in sulfides during ion irradiation from the solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the lack of a significant O reduction in these previous surface concentration measurements for several different silicates,it appears unlikely that the O SBE could be 1 eV. However, it is unknown if a process such has radiation-enhanced diffusion may replenish the sputtered surface O in those experiments, and thus making these low SBEs possible (Quadery et al 2015;Chaves & Thompson 2022;Christoph et al 2022). Here, we consider the 6.5 eV SBE to be the most likely, but for the sake of completeness we include O SBE values of 2.6 subsequent simulations.…”
Section: Effect Of the Oxygen Surface Binding Energymentioning
confidence: 92%